Reframing Local Communicative Culture as a Resource for Pluricultural Competence: A Conceptual Exploration of Malang’s Cultural Practices in BIPA Contexts - Fabian Omar Batitusta; Prima Vidya Asteria; Syamsul Sodiq; Chamaipak Maiklad (Universitas Muhammadiyah Malang, 2025)
Indonesian Language Learning for Foreign Speakers (BIPA) requires a contextual and intercultural approach that connects learners to the sociocultural realities of Indonesian society. However, current BIPA curricula and teaching materials remain largely dominated by a general thematic approach that does not systematically represent local cultural values. This research aims to identify the cultural practices of local communication in Malang that have pedagogical relevance and design a conceptual model of BIPA level 1 teaching modules based on pluricultural competence. The method used is a qualitative interpretive approach with an exploratory conceptual design. Data collection was carried out through literature studies, semi-structured interviews with teachers and cultural figures, participatory observation of communication practices in public spaces, and analysis of BIPA teaching materials and curriculum documents. The results of the study show that elements of communication culture, such as boso walikan, local politeness, and social interaction patterns of the Malang community, contain the values of egalitarianism, community solidarity, and local humor that support the formation of intercultural awareness, the ability to mediate meaning, and the reflection of learners' cultural identity. These findings were then formulated into a conceptual model that integrates elements of local culture into BIPA's learning strategies. In conclusion, integrating Malang's local communication culture can enhance the pluricultural competence of foreign learners and enrich language learning designs that are dialogical, reflective, and contextually based.